Improving Resilience to Climate Impacts in Ghana through Improved Availability, Access and Use of Climate Information: Dialog with Users - Nenkam, Andree M.; Lamptey, Patrick; Torgbor, Francis; Larbi, Frederick Out; Asante, Vincent Antwi; Kumi, Naomi; Sibiry Traoré, Pierre C. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2016)
The Ghana Meteorological Agency (GMET) in collaboration with the international Research Institute for Climate and Society and the International Crop Research Institute for the Semi-Arid Tropics has organised a one day workshop on December 19th 2016 to officially launch the initiative “Enhancing Climate National Services (ENACTS)”. The Initiative ENACTS brings climate and knowledge into national decision making by improving availability, access and use of climate information. The availability is enhanced by merging station data with other proxies, and its access is through the online state of the art tool, the Meteo Ghana Climate Data Library installed GMET and publicly available online. The objectives of the workshop were to (i) introduce this new GMET’s data and web interface to stakeholders; and (ii) soliciting feedback and needs from participants. Participants were very amazed about the online tool and requested for a training to learn how to make use of it in their day to day activities and improve their decision making.